Euro Area Imbalances - Mark Mink; Jan Jacobs; Jakob de Haan (Center for Economic Studies and ifo Institute (CESifo), 2016)
We argue that if currency union member states have different potential output per capita, output growth rates, or trade balances, the common monetary policy may not be optimal for all of them. Euro area imbalances for potential output and for trade balances are quite large, while output growth imbalances are more modest. Member states with larger imbalances of one type also have larger imbalances of both other types, but a decline of one imbalance need not coincide with a decline of the others. We also show that imbalances are fairly persistent, and are larger in poorer and smaller member states.
Keywords: E30; F45; O47; 330; euro area macroeconomic imbalances; common monetary policy; economic convergence; business cycle synchronization; euro crisis